2011
DOI: 10.1525/mp.2011.29.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Music Lessons and Intelligence: A Relation Mediated by Executive Functions

Abstract: the present study investigated whether the association between music lessons and intelligence is mediated by executive functions. Intelligence and five different executive functions (set shifting, selective attention, planning, inhibition, and fluency) were assessed in 9- to 12-year-old children with varying amounts of music lessons. Significant associations emerged between music lessons and all of the measures of executive function. Executive functions mediated the association between music lessons and intell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
167
1
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(200 citation statements)
references
References 24 publications
20
167
1
11
Order By: Relevance
“…This has, of course, also been the case in previous correlational studies (e.g. Degé et al 2011;Schellenberg 2006aSchellenberg , 2011.…”
Section: Extended Music Educationsupporting
confidence: 75%
See 1 more Smart Citation
“…This has, of course, also been the case in previous correlational studies (e.g. Degé et al 2011;Schellenberg 2006aSchellenberg , 2011.…”
Section: Extended Music Educationsupporting
confidence: 75%
“…Practice in music has been found to speed-up literacy skills (Moreno et al 2009) and the studying of foreign languages (Slevc and Miyake 2006;Milovanov et al 2008). Some more general transfer effects have also been found; music education has been found to enhance selective attention (Degé et al 2011) and sensitivity to emotions in speech (Thompson, Schellenberg, and Husain 2004).…”
Section: Social Benefits Of Musicmentioning
confidence: 99%
“…However, our understanding of this relationship is limited because most previous studies have examined only individual components of EF and have examined relatively small groups of participants. In addition, the only two relatively large studies that examined how musical experience relates to multiple aspects of EF (in children) yielded inconsistent findings (Degé et al, 2011;Schellenberg, 2011). Drawing conclusions from this past work is difficult not only because of the variety of EF components examined, but also the variety of tasks used to measure EF and the variety of criteria used to categorize participants as "musicians" or "nonmusicians".…”
Section: Discussionmentioning
confidence: 99%
“…First, past studies have typically discussed EFs only generally without systematically differentiating between various aspects of EF. To our knowledge, only two studies have systematically investigated multiple components of EF: one found that duration of music lessons in children correlated with performance on multiple EF tasks (Degé, Kubicek, & Schwarzer, 2011) but another found no such relationships (Schellenberg, 2011). Relatedly, the modality-specificity or generality of these effects remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although these group differences could reflect innate predispositions rather than causal effects of training, they are supported by longitudinal evidence for improved inhibitory control with short-term music training (Moreno et al, 2011). Furthermore, it has been suggested that enhancements in inhibitory control may underlie the transfer of benefits from musical practice to more general cognitive functions (Moreno & Farzan, 2015;Degé, Kubicek, & Schwarzer, 2011). It is therefore of interest to determine which elements of musical experience may lead to these enhancements.…”
Section: Introductionmentioning
confidence: 99%